Interactive mobile media tagging - Tan, Jun Hong. (2011)
This project takes a look at how mobile media search and sharing works. Media searching and sharing nowadays is no longer bound to a desktop or notebook. It can be done on the move with a smart mobile phone. It will discuss on how interactive tagging can be developed for these purposes. The method will involve peer or community tagging where each individual mobile users can insert tags/keywords to the image data. The main idea here is to gather information of annotated images that users had uploaded and from these images, try to provide tags/keywords for other images. The project was based on the Bag-of-Words framework where each image is modelled as a collection of features. A more detailed review on the database used, chosen method and other available methods is also discussed.